DAMPAK PENGUNGKAPAN SUKARELA DAN MANAJEMEN LABA TERHADAP INFORMASI ASIMETRI - Wiwik Utami (Media Riset Akuntansi, Auditing & Informasi, 2006)
The objectives of the research are to find out empirical evidence of he impact of voluntary disclosures and earnings management on the information asymmetry. The population of this study was public companyof manufacturing sector listed at Jakarta Stock Exchange, and the sample as determined based on the following criteria: (a) the annual reportended 31 December; and (b) book value of equity is positive. There were 92 companies meeting the criteria. Data analysis was carried out in terms of pool cross-section covering stock transaction and annual financial report during 2001-2002. The research hypotheses were tested using the regression analysis. The result of this research show that: (1) voluntary disclosures had significantly negative influence on information asymmetry, is finding gives empirical evidence that supports the theory that voluntary disclosures had impact on increasing investor's belief so that information asymmetry is diclined; (2) earnings management had no impact on information asymmetrykeywords: Voluntary disclosures, Earnings management